Educating Small and Medium Enterprises (SMEs) in Understanding Financial Literacy - Budi Setiawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Financial literacy and inclusion are crucial for Small and Medium Enterprises (SMEs) to remain competitive. However, many SMEs have a limited understanding of the concepts and applications of financial literacy, facing challenges in financial management and business development. This community service activity aims to educate SMEs about financial literacy, using an approach based on the problems faced by SMEs in Palembang and reports from the Financial Services Authority (OJK) regarding the gap between financial inclusion and literacy in Indonesia. The results of this service show that educational programs focused on real-life examples are highly effective in improving SMEs' understanding of financial literacy. The appropriate use of approaches and ongoing mentoring also significantly contribute to increasing SMEs' knowledge. Questionnaire evaluations show an increase in financial literacy, including knowledge of numeracy, inflation, and risk diversification between pre- and post-training. Therefore, structured and sustainable training programs are essential for supporting the growth and sustainability of SMEs. This program enables SMEs to leverage knowledge and understanding for better financial management and sustainable business innovation. Additionally, such training supports the United Nations program on Sustainable Development Goal Number 8 related to economic growth.